1160 LEARN (Urological Teaching in British Medical Schools Nationally): A Multicentre Cross-Sectional Study. (12th October 2021) - Ng, A; Chan, V W S; Asif, A; Lam, C M; Light, A; Jayaraajan, K; Cambridge, W A; Matthew, M G; Clement, K D; Kulkarni, M; Bhatt, N R; Khadhouri, S; et al.
Abstract: Introduction: Urology is a common rotation for UK Foundation Year (FY) doctors, and accounts for >25% of acute surgical referrals. In 2012, the British Association of Urological Surgeons (BAUS) produced 'An Undergraduate Syllabus for Urology', advising on common clinical areas of urology to be covered during medical school. However, its national uptake remains unknown. LEARN aims to assess undergraduate urology teaching across UK medical schools. Method: LEARN is the largest ever multicentre cross-sectional study of undergraduate urology teaching. Year 2-5 medical students and FY1 doctors were invited to complete a survey between 3rd October-20th December 2020. The primary objective is to compare current undergraduate urology teaching against the BAUS syllabus. Secondary objectives investigate the type and quantity of teaching provided, the reported performance rate of GMC mandated urological procedures, and the proportion of those considering urology as a career. Results: A total of 7, 611/8, 346 (91.2%) responses from 39 medical schools that met the inclusion criteria were analysed. 16.5% of responses were newly appointed FY1 doctors. In their undergraduate training, the most commonly taught topics were urinary tract infection, acute kidney injury and haematuria; the least taught topics were male urinary incontinence, male infertility and erectile dysfunction. 90.6% and 86.3% had reported performing catheterisation as undergraduates on male and female patients respectively, and 16.9% had considered a career in urology. Conclusion: LEARN provides the largest evaluation of any undergraduate specialty teaching. It has identified areas to improve teaching, to equip the future workforce with the competencies to manage urological pathology, irrespective of future career choice.